Sistema nervoso central de Hypoptopomatinae e Neoplecostominae (Siluriformes: Loricariidae): implicações filogenéticas - Rosa, Alaina Cristine [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Since the first phylogenetic hypotheses for Hypoptopomatinae and Neoplecostominae, many changes have occurred due to the increase of its known diversity, which had great impact on the latest phylogenetic proposals. Came to light also problems involving the composition of both subfamilies due to differences between morphological and molecular analysis. Thus, new sources of data are fundamental to a better understanding of the diversity of groups, and contribute to the elucidation of their evolutionary history. Therefore, this study aimed to evaluate the contribution of neuroanatomical characters in a phylogenetic analysis to Hypoptopomatinae and Neoplecostominae, in order to assess its composition, the phylogenetic relationships within the subfamilies, and of these groups with other subfamilies of Loricariidae. Were analyzed 55 terminal taxa including the Loricariidae subfamilies Delturinae, Hypoptopomatinae, Hypostominae, Loricariinae, Neoplecostominae, representatives of Callichthyidae, which also belongs to the superfamily Loricarioidea, and Pimelodidae. The specimens were dissected and had their brain removed for morphological analysis. Phylogenetic analysis was performed using heuristic search, using the TNT software, version 1.1. 60 characters treated as non-additive and with equal weights were used. The results support the monophyly of Loricariidae, and three of its subfamilies (Hypoptopomatinae, Loricariinae and Neoplecostominae). The analysis showed particularly good resolution at the level of subfamily, although the relationship between them presented fluctuations, which appears to be primarily related to Loricariinae taxa, which as a result is the most diverse group regarding to the central nervous system. Loricariinae was recovered as the most basal subfamily. The subfamily Neoplecostominae was found composed by Pareiorhaphis hystrix, Isbrueckerichthys and Neoplecostomus, this one recovere ...

Desde as primeiras hipóteses filogenéticas para Hypoptopomatinae e Neoplecostominae, muitas mudanças ocorreram em decorrência do aumento da diversidade conhecida, o que teve grande impacto nas filogenias propostas posteriormente. Surgiram também problemáticas envolvendo a composição de ambas as subfamílias em virtude de divergências entre análises morfológicas e moleculares. Sendo assim, novas fontes de dados são fundamentais para um maior entendimento da diversidade dos grupos, além de colaborar para a elucidação de sua história evolutiva. Desta forma, o presente trabalho teve como objetivo avaliar a contribuição de caracteres neuroanatômicos em uma análise filogenética para Hypoptopomatinae e Neoplecostominae, de modo a avaliar sua composição, as relações filogenéticas entre as subfamílias e delas com as outras subfamílias de Loricariidae. Para tanto, foram analisados 55 táxons terminais pertencentes às subfamílias Delturinae, Hypoptopomatinae, Hypostominae, Loricariinae e Neoplecostominae, além de representantes de Callichthyidae, pertencentes também à superfamília Loricarioidea, e Pimelodidae. Os espécimes foram dissecados e tiveram seu encéfalo retirado para a análise morfológica. A análise filogenética foi realizada por meio de busca heurística, usando-se o software TNT, versão 1.1. Foram utilizados 60 caracteres tratados como não-aditivos e com pesos iguais. Os resultados corroboram o monofiletismo de Loricariidae, e de três de suas subfamílias (Hypoptopomatinae, Loricariinae e Neoplecostominae). A análise demonstrou boa resolução principalmente no nível de subfamília, embora o relacionamento entre elas tenha apresentado flutuações, o que parece estar relacionado principalmente aos táxons de Loricariinae, que tem resultado como o grupo mais diverso no que se refere ao sistema nervoso central. Loricariinae foi recuperada como subfamília mais basal...
Keywords: Ecologia animal; Peixe - Filogenia; Cascudo (Peixe); Sistema nervoso central